Tourism Development Policy and Their Impact on the Regional Economy in the Riau Islands Province - Wulandari, Sekar Nur; Afriyanni (Research and Development Agency Ministry of Home Affairs, 2021)
Riau Islands is a province that is blessed with tourism potential, both natural tourism and cultural tourism. In 2018, the Riau Archipelago Province (Kepri) had 17 Superior Regional Tourism Destinations (DPUD) spread across seven regencies and cities. The natural, cultural, and culinary wealth potential for the tourism industry and supported by a very strategic geographical location because it borders Malaysia, Singapore, and Vietnam, makes Riau Islands Province the second most visited tourist destination by foreign tourists after Bali Island. Through the tourism sector, the Riau Islands should maximize this potential to generate PAD and contribute to high state financial contributions. However, in the field conditions, as evidenced by the insignificant GRDP growth of the Tourism Sector, it can prosper the community and has not made tourism a leading sector. This study will discuss how the local government develops tourism to grow the economy of the Riau Islands. The successful implementation of tourism development policies will be seen from the tourism sector's contribution to the regional economy, the impacts, and the obstacles faced in its implementation. The purpose of this study is to identify tourism policies and analyze their impact on tourism development as well as the obstacles faced as a guide in preparing tourism development policy recommendations to support the economy of the Riau Islands Province. By applying a combination of empirical, policy, and literature approaches, it can be concluded that the real impact of tourism development policies will be seen from, among others, the number of tourist visits, the average length of stay, average hotel occupancy, the contribution of the tourism sector to GDP, total tourist expenditure and the percentage increase in the creative economy and the contribution of the tourism sector to PAD. It is necessary to increase collaboration in tourism policy governance in the Riau Islands. The collaborations still considered weak include implementing tourism events, promotions, tourism human resource development, and institutions.